THE EFFECT OF HEMODIALYSIS THERAPY ON CHANGES IN ELDERLY URIC ACID LEVELS PRE AND POST IN PATIENTS WITH CHRONIC RENAL FAILUREAGED 45-59 YEARS OLD IN GENERAL HOSPITAL - agus fathur rahman (CNJ: Caring Nursing Journal, 2018)
Chronic renal failure is a characteristic, progressive, and irreversible disorder that causes the kidney's ability to remove waste products and maintain fluid and electrolyte balance. The frequent impact is accumulation of metabolic waste, including uremia, excess fluid load, acidosis, hyperkalemia, and hyperuricemia. The aim of the study was to determine and examine more deeply the effect of hemodialysis therapy on changes in elderly uric acid levels in patients with chronic renal failure, a perception that has been focused on gout for several years as a sign of vascular problems in patients with kidney failure.This type of study was Quasy Experimental study with Pre and post test without control approach. The sample in the study were 15 respondents with purposive sampling technique. The results of the study was Wilcoxon test obtained p value of 0.003 (<0.005) there was a significant effect after hemodialysis, which was reduce in uric acid levels, in the elderly who got hemodialysis therapy in RSUD Kotabaru in 2018. The conclusion of this study is that there is an effect of hemodialysis therapy on changes in uric acid levels in men aged 45-59 years with chronic renal failure at Kotabaru Hospital. It was suggested to the hospital to continue to improve hemodialysis therapy services and to pay attention to uric acid levels to determine changes in uric acid levels so as to support the success of hemodialysis therapy.